INVESTASI DALAM SAHAM & OBLIGASI DAN MEMINIMALISASI RISIKO SEKURITAS PADA PASAR MODAL INDONESIA - Mudjiyono, Mudjiyono (Sekolah Tinggi Ilmu Ekonomi Semarang, 2012)
Monetary manager as one who have accountability in arranging company fund traffic have to can be optimal of usage of fund. Its meaning don't there is out of job cash. Cause otherwise hence company will experiencing of many loss. Company will lose many opportunity and opportunity of beneficial business. There are some way of to exploit excess of all fund of advantage mengais, one of them [pass/through] invesment in the form of obligation or share. Advantage obtained from part of alloted dividend as according to and also capital or shares of stock his. Other advantage can in the form of management control that is rights determine policy of company bought. Management Control obtained by if ownership  of  tired  share  amount  of  majority.  Primary  factor  causing  share  price  is different perception from each investor as according to got information.  In the world of effort, each; every us do/conduct invesment hence the invesment will always contain return or advantage  and risk.  High lower investor attitude  him to risk  base  on the inve stor preferensi to risk.